Method for Correlation of Proton Magnetic Resonance Assignments in Different Solvents: Conformational Transition of Oxytocin and Lysine Vasopressin from Dimethylsulfoxide to Water - Glickson, J. D. (1972)
The peptide amide, primary carboxamide, and aromatic proton resonances were assigned to specific hydrogens of oxytocin and lysine vasopressin (Lys-VP) in water at 23° at pH 2.5 and 4.2, respectively. We started with the spectral assignments of oxytocin and Lys-VP determined in deuterated dimethylsulfoxide (Me(2)SO) and monitored the course of each of these resonances as the proportion of water to Me(2)SO was gradually increased. Changes in each of the two hormones in chemical shifts and in some coupling constants indicate that conformational alterations occur in both oxytocin and Lys-VP during the solvent transition from Me(2)SO to water. This study is a specific application of a general method for correlating spectral assignments in different solvents and for monitoring conformational changes accompanying solvent transitions. Application of this technique requires only that the solvent components be miscible over the entire transitional range, that spectral changes of the solute be simple enough to follow, and that the associated structural changes of the solute be “rapid on the proton magnetic resonance time-scale.”